2022
DOI: 10.3390/jcm11247525
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ProP1 Gene in a Cohort of Tunisian Patients with Congenital Combined Pituitary Hormone Deficiency

Abstract: Background: Non-syndromic combined pituitary hormone deficiency (CPHD) occurs due to defects in transcription factors that govern early pituitary development and the specification of hormone-producing cells. The most common mutations are in the Prophet of Pit-1 (ProP1) gene. This work aims to (1) report findings of genetic analyses of Tunisian patients with non-syndromic CPHD and (2) describe their phenotype patterns and their evolution through life. Methods: Fifteen patients from twelve unrelated families wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…These two mutations were found in 90% of CPHD cases. On the other hand, Moalla et al (2022) recently reported two mutations (p.(Gln114Ter) and p.(Arg73Cys)) in Tunisian families with non-syndromic CPHD [ 24 ]. The p.(Arg73Cys) mutation was previously reported as the most common PROP1 mutation among CPHD patients from North Africa [ 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…These two mutations were found in 90% of CPHD cases. On the other hand, Moalla et al (2022) recently reported two mutations (p.(Gln114Ter) and p.(Arg73Cys)) in Tunisian families with non-syndromic CPHD [ 24 ]. The p.(Arg73Cys) mutation was previously reported as the most common PROP1 mutation among CPHD patients from North Africa [ 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%